Analyzing the factors affecting level of debt for selected construction companies in Malaysia / Zahariah Sahudin, Anidah Aziz and Faridah Pardi - Sahudin, Zahariah; Aziz, Anidah; Pardi, Faridah (Research Management Institute (RMI), 2009)
The main objective of this paper is to find the possible relationship between several factors that might have effect on level of debt among construction companies in Malaysia. Previous studies identified number of factors that affect level of debt (leverage) - such as size of firms, growth opportunity, firm's reputation, generated resources, level of warrants, debt cost and others. In addition, these studies also identify the concept of leveraging and capital structure formation among companies worldwide. Recent papers investigated whether some of the factors mentioned have significant impact on firm's leverage. They found that not all variables have significant correlation that fits the basic model. The study used the data from ten selected Malaysia's construction companies from 2001 until 2008. The model used in this research paper was the one derived from previous study. The estimation results show that the size of construction companies have significantly strong positive relationship to the firm's leverage. The finding is consistent with the previous findings that firm's size adds huge information in explaining the level of debt. The results also suggest that company's leverage is positively affected by firm's reputation. On the other hand, growth opportunity had inverse relationship with leverage, showing that greater leverage would mean a declining growth opportunity for firms. Finally, the analysis results suggest that, by including some other factors, and by taking a bigger sample subset of population might improve the results in future research.